Pengaruh Price Earnings Ratio dan Price to Book Value terhadap Return Saham Indeks LQ 45 (Perioda 2007-2009) - Meythi -; Mariana Mathilda (Universitas Kristen Maranatha, 2012)
This study purposes to determine the effect of Price Earnings Ratio (PER) and Price to Book Value (PBV) simultaneously and partially towards LQ 45 index stock return. The sample is taken from LQ 45 index constituent company for period August 2006 until January 2007 at Indonesian Stock Exchange. Dependent variable in this study is stock return, while Price Earnings Ratio (PER) and Price to Book Value (PBV) as independent variables. This study used Moderated Regression Analysis as a method of data analysis.Based on the results of testing and analysis of data concerning the influence of Price Earnings Ratio (PER) and Price to Book Value (PBV) of stock return, found that the partial Price Earnings Ratio (PER) has a negative influence and Price to Book Value (PBV) has no effect on stock returns while simultaneously Price Earnings Ratio (PER) and Price to Book Value (PBV) has no effect on stock returns.